Bioremediation of Liquid Waste in Sanan Tempeh Industry and Its Unit Operation Planning (Study on Aeration Rate and Incubation Time) - Wignyanto, Wignyanto; Hidayat, Nur; Ariningrum, Alfia (Jurnal Teknologi Pertanian, 2009)
This objective of the research was to design and implement Waste Water Treatment Unit for Sanan’s tempeh using bioremediation technique to produce free pollutant waste complying with standard environmental regulation for tempeh liquid waste before it is dumped into the waterways. This experiment is designed using Randomized Group Design. It consists of two factors which are, firstly, variation of aeration speed ( 1 vvm, 2 vvm, 3 vvm), secondly, variation of incubation time ( 0 days , 3 days, 7 days). It was shown that the best treatment, the combination of 3 vvm of aeration speed and 7 days of incubation time capable to reduce up to 83.9 % of BOD; 73,1% of COD; 93.1% of TSS and 45.8 % of detergent. The value of BOD and COD has satisfactorily complied with standard environmental regulation for tempeh liquid waste, which is the value of TSS and detergent just nearly complying. The Treatment Unit designed for treating tempeh liquid waste of about 45 m3 /day in average is consists of pre-sediment tank with the capacity of 100 m3, 7 aeration tank with air compressor, final-sediment tank, controlled tank which has a capacity the same as pre-sediment tank and calcium-bicarbonate solution tank. The area for building Waste Water Treatment Unit is 1440 m2.Keywords: bioremediation, liquid waste, tempeh industry, waste water treatment unit.